Estimation on Mortality of Tropical Limpet Cellana testudinaria (Class : Gastropoda, Family : Patellidae) Living on the Rocky Shore of Ohoiwait, Southeast Moluccas, Indonesia - Abraham Seumel Khouw (Marine Science Department Diponegoro University, 2004)
Sebanyak 2402 ekor limpet diperoleh dari 12 bulan pengambilan sampel yakni dari Oktober 2001 sampai September 2002. Rata-rata mortalitas limpet C. testudlnaria diestimasi dengan mempergunakan tiga metoda yang berbeda dengan hasil adalah sebesar 94% per tahun (Z =2.81). Mortalitas terbesar yang dilakukan dengan menggunakan pendekatan metoda Ault-Ehrhardt dijumpai pada bulan Oktober 2001 dan April 2002, dimana terjadi kekeringan dan hempasan gelombang yang terbesar. Akan tetapi tidak ada korelasi yang jetas antara mortalitas dan faktor-faktor lingkungan. A total oF 2202 limpets were obtained in 12 monthly collections (from October 2001 to September 2002). The mean mortality oF C. testudinaria was estimated, using three different methods; reduction in the survival of individual size frequency cohorts through time, monthly calculation of the Ault and Ehrhardt moment estimation, and length-converted catch curves. to be 94% per year (Z = 2.81). Highest monthly mortality rates, determined with the Ault-Ehrhardt approach, were observed in October 2001 and April 2002, when desiccation stress (temperature of the rocky surface was about 4O0C) and wave action (was about 3 m), respectively, were highest However, there was no significant linear correlation between mortality and environmental variables.